Epidemiological impact of a syphilis vaccine: a simulation study - CHAMPREDON, D. (Epidemiol Infect, 2016)
Despite the availability of inexpensive antimicrobial treatment, syphilis remains prevalent worldwide, affecting millions of individuals. Furthermore, syphilis infection is suspected of increasing both susceptibility to, and tendency to transmit, HIV. Development of a syphilis vaccine would be a potentially promising step towards control, but the value of dedicating resources to vaccine development should be evaluated in the context of the anticipated benefits. Here, we use a detailed mathematical model to explore the potential impact of rolling out a hypothetical syphilis vaccine on morbidity from both syphilis and HIV and compare it to the impact of expanded ‘screen and treat’ programmes using existing treatments. Our results suggest that an efficacious vaccine has the potential to sharply reduce syphilis prevalence under a wide range of scenarios, while expanded treatment interventions are likely to be substantially less effective. Our modelled interventions in our simulated study populations are expected to have little effect on HIV, and in some scenarios lead to small increases in HIV incidence, suggesting that interventions against syphilis should be accompanied with interventions against other sexually transmitted infections to prevent the possibility that lower morbidity or lower perceived risk from syphilis could lead to increases in other sexually transmitted diseases.